Atlas of hybrid imaging of the thorax, abdomen and pelvis : sectional anatomy for PET/CT, PET/MRI and SPECT/CT.: sectional anatomy for PET/CT, PET/MRI and SPECT/CT. Volume 2 (2022) - Leporace, Mario; Calabria, Ferdinando; Gaudio, Eugenio; Schillaci, Orazio; Ciaccio, Alfonso; Bagnato, Antonio
No abstract available